Analisis Perilaku Sanitasi Wisatawan Kawasan Ekonomi Khusus Mandalika - Lalu Muhammad Aby Dujana; Ernawati Ernawati; Isrowati Isrowati; Baiq Fadila Arlina; Hilman Ahyadi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The Mandalika tourism area in Central Lombok Regency has been designated as a Special Economic Zone (KEK), leading to rapid development through improved facilities and services, which in turn has significantly increased visitor numbers. While this growth has generated positive impacts, it also poses environmental challenges, particularly regarding sanitation. This study aims to examine tourist sanitation behavior in the KEK Mandalika, focusing on waste bin usage and wastewater management. Data were collected using a questionnaire based on a Likert scale, allowing for quantitative assessment and statistical analysis of behavioral variables. The results show that 59% of respondents demonstrated “Good” behavior in waste bin usage, while 41% were categorized as “Less Good.” In terms of wastewater management, 64% of respondents exhibited “Good” behavior, and 36% fell into the “Less Good” category. However, reporting damaged waste bin facilities and participation in wastewater management programs remain insufficient, as these practices are rarely carried out by visitors.